Análise crítica da relação entre endividamento oneroso, Ebitda e cobertura de juros para empresas de capital aberto do setor industrial de atividade cíclica - Silva, Sandra Egydio Pereira da (2017)
The objective of this research is to analyze the relationship between onerous indebtedness, Ebitda and interest coverage to verify if, in fact, there is the true fiscal benefit for public companies in the industrial sector of cyclical activity, especially in this moment of crisis, namely 2015 and 2016. The sample for this analysis was composed of seven industrial companies in the cyclical sector, listed on BM & FBovespa. For this purpose, the annual balance sheets for 2007 to 2016 of these selected companies were observed in order to verify the behavior of short and long term indebtedness, Ebitda in relation to financial expenses, tax benefit (income tax with and without inclusion of financial expenses in the calculation basis). The results of these analyzes showed that, in the crisis years 2015 and 2016, companies tended to raise more shortterm debt, that Ebitda in most companies covered financial expenses, and that the tax saved on financial expenses occurred even when there was loss. Dependent and independent variables through Stepwise statistics were also analysed in order to verify the degree of dependence of Ebitda, income tax and financial expenses. The main results of the statistics showed that the variable Ebitda has a positive dependence on income tax and financial expenses. Income tax was dependent on Ebitda and, finally, financial expenses were dependent on short-term loans, net indebtedness and Ebitda. Even in the face of a systemic crisis, through the satisfactory management of indebtedness, it is possible for companies to present positive operating results, fully covering financial expenses